Switchable frequency selective surface design for 2.45GHz ISM band - Doken, Bora; Kartal, Mesut (IEEE, 2017)
Mutual interference between adjacent wireless networks in indoor environment is becoming an important issue due to reducing the communication speed significantly. Isolating the wireless networks by using frequency selective surfaces (FSSs) can be an efficient solution for such interference problems. Isolating and non-isolating features are needed from FSSs due intensive usage of wireless communication systems. As a solution proposal, a novel switchable band stop FSS design is presented in this work. Switching feature is achieved by inclusion PIN diodes on the conducting path of circular loop element geometry. Eight number of PIN diodes are placed 45 degrees intervals in order to achieve polarization stability and desired switching performance. Analyzes of the proposed surfaces are executed with Ansoft HFSS v.15 software. According to the simulation results, desired frequency response is achieved.